Dialysis decision in critically ill patients in intensive care unit - Harin Rhee (Acute and Critical Care)
The 2012 Kidney Disease Improving Global Outcomes guidelines clearly define emergent indications for kidney replacement therapy; however, whether dialysis should be initiated in critically ill patients without these indications remains unclear. This review briefly summarizes the results of recent landmark trials and discusses their limitations originating from a criteria-based approach at a single time point. Moreover, a personalized approach based on each patient’s demand-capacity balance and its future benefits as a platform for kidney support therapy in critically ill patients are discussed.